2005
DOI: 10.1158/0008-5472.can-04-2490
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Barrett's Metaplasia to Adenocarcinoma Is Associated with the Suppression of the Transcriptional Programs of Epidermal Differentiation

Abstract: We did expressional profiling on 24 paired samples of normal esophageal epithelium, Barrett's metaplasia, and esophageal adenocarcinomas. Matching tissue samples representing the three different histologic types were obtained from each patient undergoing esophagectomy for adenocarcinoma. Our analysis compared the molecular changes accompanying the transformation of normal squamous epithelium with Barrett's esophagus and adenocarcinoma in individual patients rather than in a random cohort. We tested the hypothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 44 publications
(42 reference statements)
9
148
1
Order By: Relevance
“…GATA6 has also been reported to be involved in colorectal tumour invasion and in the conversion of Barrett metaplasia to adenocarcinoma 27,28 . Furthermore, GATA6 is known to be expressed in the proliferative crypt compartment of the small intestine, similar to Lgr5, although expression is found elsewhere as well 19,25 .…”
Section: Gata6 Upregulates Lgr5 Expression In Colorectal Cancer Cellsmentioning
confidence: 99%
“…GATA6 has also been reported to be involved in colorectal tumour invasion and in the conversion of Barrett metaplasia to adenocarcinoma 27,28 . Furthermore, GATA6 is known to be expressed in the proliferative crypt compartment of the small intestine, similar to Lgr5, although expression is found elsewhere as well 19,25 .…”
Section: Gata6 Upregulates Lgr5 Expression In Colorectal Cancer Cellsmentioning
confidence: 99%
“…Overexpression of MMSET was found in glioblastoma compared to normal brain (P = 1.7E-14, P = .009, P = .002) [11; 12; 13]; in hepatocellular carcinoma compared to normal liver (P = 2.9E-7, 1.3E-6) [14; 15]; in head and neck cancer compared to the normal (P = .008, P = 2.7E-5) [16; 17]; in bladder carcinoma compared to normal bladder (P = 4.1E-11, P = 1.8E-7) [18; 19]; in primary colon cancer compared to normal adjacent mucosa (P = 9.5E-6) [20]; in esophagus adenocarcinoma compared to normal esophagus (P = .004) [21]; in breast carcinoma compared to normal breast (P = 3.8E-8) [22]; in T-cell acute lymphoblastic leukemia compared to normal bone marrow (P = 5.1E-7) [23]; in B-cell acute lymphoblastic leukaemia compared to normal bone marrow (P = .001) [23]; in lung adenocarcinoma compared to normal lung (P = .009, P = 8.4E-4, 1.7E-6) [24; 25; 26]; in lymphoma compared to normal B-cell (P = 3.5E-5, 7.3E-5) [27]; in cutaneous melanoma compared to normal melanocyte ( P = 6.46E-13, P = .01, P =.009) [28; 29; 30]; in smoldering multiple myeloma compared to normal bone marrow (P = 7.3E-4) [31]; in prostate cancer compared to normal prostate (P = 1.8E-6, P = .039, P = 5.1E-8, P = .002, P = .009, P = .006, P = .009) [32; 33; 34; 35; 36; 37; 38]; in yolk sac tumor compared to normal testis (P = .003) [39]; in ovarian carcinoma compared to normal ovary (P = .002, P = 1.1E-4) [40; 41] and in clear cell carcinoma compared to normal kidney tissue (P = .006) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of normal and esophageal tumor tissues demonstrates decreased ANXA1 expression with a concomitant increase in miR-196a levels in tumors compared to the matched normal tissue. In light of the report that ANXA1 mRNA levels progressively decrease from normal esophageal epithelium to Barrett's esophagus (BE) and from BE to adenocarcinoma (Kimchi et al, 2005), it would be interesting to determine if miR-196a level can be used as early marker of esophageal cancer. Though our study predominantly focused on esophageal adenocarcinomas, previous studies have reported an association between ANXA1 loss and tumorigenesis of squamous cell carcinoma of the esophagus (Paweletz et al, 2000;Xia et al, 2002;Hu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%